How narrow is the spectrum of submaximal speeds in swimming? - Greco, Camila C. [UNESP]; De Oliveira, Mariana F.M. [UNESP]; Caputo, Fabrizio [UNESP]; Denadai, Benedito S. [UNESP]; Dekerle, Jeanne (Wolters Kluwer, 2013)
The purpose of this study was to identify the boundary of submaximal speed zones (i.e., exercise intensity domains) between maximal aerobic speed (S-400) and lactate threshold (LT) in swimming. A 400-m all-out test, a 7 × 200 m incremental step test, and two to four 30-minute submaximal tests were performed by 12 male endurance swimmers (age = 24.5 ± 9.6 years; body mass = 71.3 ± 9.8 kg) to determine S-400, speed corresponding to LT, and maximal lactate steady state (MLSS). S-400 was 1.30 ± 0.09 m·s -1 (400 m-5:08 minutes:seconds). The speed at LT (1.08 ± 0.02 m·s-1; 83.1 ± 2.2 %S-400) was lower than the speed at MLSS (1.14 ± 0.02 m·s-1; 87.5 ± 1.9 %S-400). Maximal lactate steady state occurred at 26 ± 10% of the difference between the speed at LT and S-400. Mean blood lactate values at the speeds corresponding to LT and MLSS were 2.45 ± 1.13 mmol·L-1 and 4.30 ± 1.32 mmol·L-1, respectively. The present findings demonstrate that the range of intensity zones between LT and MLSS (i.e., heavy domain) and between MLSS and S-400 (i.e., severe domain) are very narrow in swimming with LT occurring at 83% S-400 in trained swimmers. Precision and sensitivity of the measurement of aerobic indexes (i.e., LT and MLSS) should be considered when conducting exercise training and testing in swimming. © 2013 National Strength and Conditioning Association.
Keywords: Endurance; Lactate threshold; Maximal lactate steady state; Performance